Design and Develop Of A Web-Based Information System E-Document At PT. Fajar Berkat Abadi - Altiono, Muhammad Rifki; Bani, Alexius Ulan; Sharyanto, Sharyanto (Yayasan Bina Internusa Mabarindo, 2025)
PT Fajar Berkat Abadi is a food and beverage supply company, with the flagship product Forestly Indonesia, an instant chocolate powder drink. This research aims to overcome the challenges of manual document management that is prone to human error. The system is designed with a web-based approach to improve efficiency in document handling. The methods used in this research are observation, interview, literature study, design and testing. Then in this study there is also a system modeling with the UML (Unifield Modeling Language) method and PHP as a programming language and Mysql as a database. The results of the research include user interface design (UI) and application prototypes that have been tested, showing a valid success rate. The implementation of this system is expected to improve document management at PT Fajar Berkat Abadi, increase effectiveness, efficiency, and provide significant benefits to the company.